Differences and Interactions of language learning with Discourse Competence on students' motivation and achievement in Islamic Junior High School in Brawijaya City Mojokerto and MTs Al Amin Sooko Mojokerto Regency - Muthoharun Afif (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
Language is expected to help students recognize themselves, their culture and other cultures, express ideas and feelings, participate in societies that use the language, make responsible decisions on a personal and social level, discover and use the analytical and imaginative abilities present in him. The purpose of this research are: 1) To know the difference of students' learning motivation of Islamic Junior High School of Brawijaya Mojokerto and MTs Al Amin Sooko, Mojokerto Regency uses language learning with Discourse Competence. 2) To know the difference of learning achievement of students of Islamic Junior High School of Brawijaya City of Mojokerto and MTs Al Amin Sooko of Mojokerto Regency use language learning with Discourse Competence. 3) To know the interaction of language learning with Discourse Competence on student learning motivation and achievement in Islamic Junior High School of Mojokerto and MTs Al Amin Sooko, Mojokerto Regency. In this research object is students of Islamic Junior High School of Brawijaya City of Mojokerto and MTs Al Amin Sooko Mojokerto Regency Class VII of 150 students and 151 students. of the population members taken as samples were 93 respondents. From the results of the analysis, it is known that: 1) language learning with Discourse Competence has an effect on students' learning motivation in Brawijaya Islamic Junior High School Mojokerto lower than in MTs Al Amin Sooko Mojokerto Regency. 2) language learning with Discourse Competence has an effect on learning achievement in Brawijaya Islamic Junior High School Mojokerto lower than in MTs Al Amin Sooko Mojokerto Regency. 3). There is interaction of language learning with Discourse Competence to student's motivation and achievement in Islamic Junior High School of Brawijaya Mojokerto and MTs Al Amin Sooko Mojokerto Regency